Tendensi Pola Komunikasi Interaksional di SMK PGRI 2 Jember (Kajian Etnografi Komunikasi) - Yusnita, Titis Rizka; Haryono, Akhmad; Badrudin, Ali (Universitas Muhammadiyah Surakarta, 2024)
Each individual's language skills influence the effectiveness of ongoing communication interactions andthis is in line with optimizing the communication goals themselves. This research aims to identify trendsin interactional communication patterns that occur at SMK PGRI 2 Jember and describe the types ofconversation topics and language boundaries that influence the meanings that emerge behind thespeaker's actions. This research was analyzed using qualitative descriptive methods. The data in thisresearch is in the form of communication interactions that occur consistently and contain interactionalcommunication patterns. The data acquisition stage is through observation and recording the finding ofcommunication patterns. Data were analyzed using the ethnographic communication theory proposedby Spradley and supported by literature study. The stage of presenting the results of data analysis usesinformal methods. The research results show that interactional communication patterns are brokendown into several mappings, namely between students and students, students and teachers, andteachers and teachers. The communication patterns that occur tend to have a systematic consistencythat is formed naturally and operates interactionally. The topics of discussion that emerged ininteractions between participants focused on several specific themes, namely learning, administration,finance, entertainment and friendship problems. Meanwhile, topics that are avoided in conversationinclude political contexts, bullying and social mistakes. The languages used in communicationinteractions consist of Indonesian, Madurese, Javanese and English. This is influenced by the geographical location of SMK PGRI 2 Jember which is located near the center of Jember Regency.